2008
DOI: 10.1016/j.ajhg.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

C6ORF66 Is an Assembly Factor of Mitochondrial Complex I

Abstract: Homozygosity mapping was performed in five patients from a consanguineous family who presented with infantile mitochondrial encephalomyopathy attributed to isolated NADH:ubiquinone oxidoreductase (complex I) deficiency. This resulted in the identification of a missense mutation in a conserved residue of the C6ORF66 gene, which encodes a 20.2 kDa mitochondrial protein. The mutation was also detected in a patient who presented with antenatal cardiomyopathy. In muscle of two patients, the levels of the C6ORF66 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
105
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 24 publications
1
105
1
Order By: Relevance
“…The first pathogenic human mutation in a CI assembly factor was found in NDUFAF2 [47]. Since this initial discovery, several other pathogenic mutations have been identified in CI assembly factor genes, including NDUFAF1 [48], NDUFAF3 [49], NDUFAF4 [50], NDUFAF5 [51], NDUFAF6 [52], FOXRED1 [53], ACAD9 [54] and NUBPL [53] (Table 1). The identification of these mutations, and the examination of how they disrupt CI assembly, have greatly aided our understanding of CI biogenesis.…”
Section: Oxphos Complex Imentioning
confidence: 99%
“…The first pathogenic human mutation in a CI assembly factor was found in NDUFAF2 [47]. Since this initial discovery, several other pathogenic mutations have been identified in CI assembly factor genes, including NDUFAF1 [48], NDUFAF3 [49], NDUFAF4 [50], NDUFAF5 [51], NDUFAF6 [52], FOXRED1 [53], ACAD9 [54] and NUBPL [53] (Table 1). The identification of these mutations, and the examination of how they disrupt CI assembly, have greatly aided our understanding of CI biogenesis.…”
Section: Oxphos Complex Imentioning
confidence: 99%
“…Control and patient cells were infected with the lentiviral construct carrying the wild-type MRPS22, and clones of stably transfected cells were established by blasticin (4 mg/ml) selection and by selection on glucose-free medium. 7,25 Patient cells were also transiently transfected with the lentiviral vector carrying an expression control plasmid, pLenti6/V5-GW/lacZ (Invitrogen).…”
Section: Transfection With Wild-type Mrps22 Cdnamentioning
confidence: 99%
“…[5][6][7][8] Furthermore, mutations have been described in eight assembly factors (NDUFAF1, NDUFAF2, NDUFAF3, NDUFAF4, C8orf38, C20orf7, ACAD9, and NDUBPL) of this complex and in an uncharacterized protein (FOXRED1) causing complex I deficiency. [9][10][11][12][13][14][15][16] Although pathogenic mutations have been described in accessory subunits, the function of these subunits is not exactly known yet. It has been suggested that some are important for the biogenesis of complex I.…”
mentioning
confidence: 99%